In vitro: evaluation of different mouth washes on dental biofilm from of orthodontic ligature / S.F. Hussain... [et al.] - Hussain, S.F.; Al-Bayaty, F.H.; Abdul Rahim, N.R.; Abdulla, M.A; Belgum, Hasnah (2012)
Clinical study has shown that patients who get the orthodontic treatment are more susceptible for having the enamel white spot formation. Since the advent of fixed orthodontic appliance for adult patients and its use has become increasingly popular, bringing about the need to address quations regarding microorganism adherence and biofilm development.